Strategi Penanggulangan Dampak Pembangunan Jalan Tol Terhadap Sosial dan Ekonomi Masyarakat Lokal - Daud Em Paulia; Fahrudin (Journal of Trends Economics and Accounting Research, 2025)
This research is based on the construction of the Probolinggo–Banyuwangi (Probowangi) toll road, part of which passes through Sentong Village, Krejengan District, Probolinggo Regency. The project is a national infrastructure megaproject aimed at connecting Kraksaan (Probolinggo) to Ketapang (Banyuwangi) in East Java. While it offers benefits such as improved accessibility and economic opportunities, the construction also brings negative impacts to local communities, including the conversion of productive land, disruption of livelihoods, damage to local infrastructure, as well as social and environmental effects. In response to these issues, this study aims to identify and analyze strategies to mitigate the social and economic impacts of toll road development on local communities, using Krejengan District as a case study. The research method used is field research with a qualitative approach, conducted through observation, interviews, and documentation. Data were collected from interviews with project managers and workers involved in the construction. The findings indicate that mitigation strategies were carried out through participatory approaches and social responsibility. These strategies included providing fair compensation, involving local labor, protecting productive land, and ensuring irrigation systems remain functional. This participatory and socially responsible approach has proven effective in minimizing negative impacts while maintaining a balance between development interests and community welfare.